PENGARUH PERILAKU INISIATIF TERHADAP KESUKSESAN AKADEMIK ANAK USIA DINI - Witarsa, Ramdhan (Tunas Siliwangi, 2016)
The long term goal of this research is to equip / reinforce / strengthen the competence of learners in order to have academic competence were good with still could have a self-regulating emotional and social good to be a man who is faithful and devoted to God Almighty, noble, healthy, capable, creative, independent, and become citizens of a democratic and responsible. Specific targets to be achieved is the mapping of students' academic competence early age in the context of self-regulation skills both emotionally and socially in Kota Cimahi. With the mapping of academic competence based skills in self-regulation in the region, it will be easier for researchers to equip / reinforce / strengthen early childhood competencies that are considered less and needs to be repaired. In addition, it also allows researchers to design the program that provides the competence of teachers as to what is needed by teachers in the early childhood field. The method used in achieving both these objectives is to use descriptive quantitative research methods. This is done in order to obtain a complete picture of what their academic competence based on self-regulation of early childhood in the city of Cimahi. This study measured children's understanding of the age of the skills of self-regulation by using a test comprehension skills of self-regulation, to analyze the ability of children bring out aspects of skills of self-regulation in the results of its work to the guidelines of performance analysis and observation guide used to analyze the child's ability to bring out aspects of skills self-regulation in learning. Keywords: Self-regulation, Academic Success.Â